Combining biological and psychosocial baseline variables did not improve prediction of outcome of a very‐low‐energy diet in a clinic referral population. Issue 1 (8th November 2017) - Sumithran, P.; Purcell, K.; Kuyruk, S.; Proietto, J.; Prendergast, L. A.
Summary: Consistent, strong predictors of obesity treatment outcomes have not been identified. It has been suggested that broadening the range of predictor variables examined may be valuable. We explored methods to predict outcomes of a very‐low‐energy diet (VLED)‐based programme in a clinically comparable setting, using a wide array of pre‐intervention biological and psychosocial participant data. A total of 61 women and 39 men (mean ± standard deviation [SD] body mass index: 39.8 ± 7.3 kg/m 2 ) underwent an 8‐week VLED and 12‐month follow‐up. At baseline, participants underwent a blood test and assessment of psychological, social and behavioural factors previously associated with treatment outcomes. Logistic regression, linear discriminant analysis, decision trees and random forests were used to model outcomes from baseline variables. Of the 100 participants, 88 completed the VLED and 42 attended the Week 60 visit. Overall prediction rates for weight loss of ≥10% at weeks 8 and 60, and attrition at Week 60, using combined data were between 77.8 and 87.6% for logistic regression, and lower for other methods. When logistic regression analyses included only baseline demographic and anthropometric variables, prediction rates were 76.2–86.1%. In this population, considering a wide range of biological and psychosocial data did not improve outcome prediction compared to simply‐obtained baseline characteristics.